A complicated cockroach‐ectomy. Issue 6 (17th May 2018) - Vazirani, Jaideep; Yu, Christiaan; Stirling, Robert
Abstract : The exact incidence of foreign body aspiration among adults is unknown, and its clinical presentation is vastly divergent. We report the previously undescribed occurrence of cockroach aspiration in an adult, presenting with a "crawling sensation" in his chest. Flexible endobronchial examination revealed a foreign body impacted in the lingula, resembling the Australian cockroach Periplaneta australasiae . Partial extraction via biopsy forceps was performed and complicated by acute hypoxia on disimpaction, requiring a brief period of bag/mask ventilation. Following the offset of procedural sedation, the remaining foreign body was manually expectorated. A total of 24 h post‐procedure, the patient was febrile with positive blood cultures ( Micrococcus luteus ). We highlight the importance of definitive airway support during endobronchial interventions and raise the question regarding the significance of transient bacteraemia following bronchoscopic manipulation. Abstract : Foreign body aspiration (FBA) is a frequent and life threatening occurrence in children. The exact incidence of FBA amongst adults is unknown. We present a previously undescribed occurrence of cockroach (Periplaneta australasiae) aspiration in an adult, followed by flexible bronchoscopic extraction. We highlight the importance of definitive airway support during endobronchial interventions and raise the question regarding significance of transient bacteraemia following bronchoscopic manipulation.